Using in-situ adsorption dilatometry for assessment of micropore size distribution in monolithic carbons. (July 2016) - Kowalczyk, Piotr; Balzer, Christian; Reichenauer, Gudrun; Terzyk, Artur P.; Gauden, Piotr A.; Neimark, Alexander V.
Abstract: We demonstrate that in-situ adsorption dilatometry provides a new opportunity for structural characterization of microporous carbons. We present experimental results for CO2 adsorption at 293 K and in-situ deformation obtained by dilatometry on a synthetic monolithic carbon sample. The carbon deformation in the course of adsorption is non-monotonic: the strain isotherm shows the sample contraction at low adsorption followed by progressive expansion. To evaluate structural and mechanical properties of the sample from the experimental adsorption and strain isotherms, a kernel of theoretical adsorption isotherms is obtained with the grand canonical Monte Carlo simulation of CO2 adsorption in a series of carbon micropores ranging from 0.22 to 2.0 nm. The respective kernel of adsorption stress isotherms is constructed using the thermodynamic model of adsorption stress. The pore volume and surface area distributions were calculated independently from a) the experimental excess adsorption isotherm by deconvoluting the generalized adsorption equation and b) the experimental strain isotherm by using the kernel of adsorption stress isotherms. The proposed method of determining the pore size distribution from the strain isotherm validates the thermodynamic model of adsorption stress in micropores and provides additional information about the sample material with respect to mechanical properties of the microporous matrix.